From Stigma to Trust: A Case Study of Hospital Rebranding and Marketing Communication in Post-Leprosy Health Institutions - Syafira Faradiba Syahruddin; Muh. Akbar; Alem Febri Sonni (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2025)
Rebranding at healthcare institutions, especially those with tainted legacies, is a multifaceted endeavor that transcends mere alterations in visual identity. Hospitals in Indonesia, historically linked to leprosy, frequently encounter difficulties in altering public opinion and restoring institutional credibility. RSUP Dr. Tadjuddin Chalid Makassar, previously a national referral facility for leprosy, exemplifies a significant change into a general public hospital. Nevertheless, few studies have investigated how these institutions employ culturally rooted and cohesive communication tactics to alter public trust. This study examines the hospital's rebranding process, focusing on institutional repositioning, cultural engagement, internal branding, and Integrated Marketing Communication (IMC). The research aims to explore how these strategies contribute to restoring the institution's image and public trust. A qualitative case study approach was employed, concentrating on the hospital’s rebranding efforts from 2018 to 2023. Data was gathered through interviews with key stakeholders, content analysis of communication materials, and a review of patient visit data. The study indicates that the intentional application of Siri, a Bugis-Makassar cultural principle emphasizing dignity, was essential in redefining the hospital's identity. IMC maintained uniform messaging across digital and offline media, while internal branding mitigated employee resistance and linked human resources with the new institutional vision. A notable rise in overall patient visits from 2018 to 2023 was recorded, indicating enhanced public perception.